A controlled clinical trial comparing potent progestins, LNG‐IUS and dienogest, for the treatment of women with adenomyosis. (7th September 2021) - Ota, Ikuko; Taniguchi, Fuminori; Ota, Yoshiaki; Nagata, Hiroki; Wada, Ikumi; Nakaso, Takaya; Ikebuchi, Ai; Sato, Eri; Azuma, Yukihiro; Harada, Tasuku
Abstract: Purpose: To evaluate the efficacy of two progestins, levonorgestrel intrauterine system (LNG‐IUS) and dienogest (DNG), for adenomyosis. Methods: This study enrolled 157 women with adenomyosis, randomized to either LNG‐IUS ( n  = 76) or DNG ( n  = 81) groups as a controlled clinical trial for 72 months. Participants were classified by three different localizations of adenomyosis: diffuse, focal, and extrinsic. VAS (Visual analog scale) score, days, and amount of uterine bleeding were assessed. Uterine volume or bone mineral density (BMD) were measured by three‐dimensional ultrasonography or dual‐energy X‐ray absorptiometry. Results: LNG‐IUS and DNG comparably reduced pain scores in patients with adenomyosis. With regard to pain control, DNG offered greater efficacy than LNG‐IUS in 3 months of treatment. In all types of adenomyosis, the days of bleeding after 12 months with DNG were significantly decreased compared to those with LNG‐IUS. The decrease of whole uterine body was transient in any subtypes. A comparable decrease in BMD due to age‐related changes in both groups was observed. Conclusions: LNG‐IUS and DNG could be useful for long‐term management of adenomyosis. In terms of durations of uterine bleeding, DNG was superior to LNG‐IUS for 6 years. Abstract : We described the efficacy of two progestins, levonorgestrel intrauterine system (LNG‐IUS) and dienogest (DNG) in the treatment of adenomyosis as a first controlled clinical trial. Patients were classified by three different localizations of adenomyosis: diffuse, focal, and extrinsic. DNG proved superior to LNG‐IUS in terms of the duration of uterine bleeding.